CORRELAÇÃO DE AVALIAÇÃO FENOTÍPICA (CPMU) COM CARACTERÍSTICAS DE CARCAÇAS POR ULTRASSONOGRAFIA - FIGUEIREDO, Ana Paula Aquino de; FERRAZ, André Luiz Julien; CARVALHO, Marcelo da Silva de; BARONI, Guilherme da Silva; ROJAS, Luiz Eduardo Souza; Rafael Braga de (ANAIS DO ENIC, 2025)
-